2009
DOI: 10.4248/ijos.09015
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus as an Independent Predictor in Oral Squamous Cell Cancer

Abstract: AimThere is an increasing evidence for the role of high risk human papillomavirus (HPV) in the pathogenesis of oral squamous cell carcinoma (OSCC). The purpose of this study is to evaluate the relevance of HPV infection to the survival and prognosis of OSCC. Methodology Fifty-two patients with OSCC were followed from 4 to 88 months with a median of 50. Conclusion HPV infection can act as an independent predictor for the survival and prognosis of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 22 publications
3
47
3
2
Order By: Relevance
“…While the meta-analysis of Chinese population indicated that the overall rate of HPV-positive OSCC was 58.0% and HPV-16 infection accounted for 47.47% of OSCC (Zhu et al, 2012). Our Li-Li Gan et al previous study with 44 patients showed that the incidence of HPV infection in OSCC in Wuhan was 40.4% (Zhao et al, 2009). This discrepancy might attribute to the different anatomic locations of tumors and techniques used to detect HPV-DNA (Termine et al, 2008).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…While the meta-analysis of Chinese population indicated that the overall rate of HPV-positive OSCC was 58.0% and HPV-16 infection accounted for 47.47% of OSCC (Zhu et al, 2012). Our Li-Li Gan et al previous study with 44 patients showed that the incidence of HPV infection in OSCC in Wuhan was 40.4% (Zhao et al, 2009). This discrepancy might attribute to the different anatomic locations of tumors and techniques used to detect HPV-DNA (Termine et al, 2008).…”
Section: Introductionmentioning
confidence: 60%
“…As the best of our knowledge, so far, it is the first time to explore relationship of HPV infection and oral cancer in Wuhan city in the south of China using case control study, which has much more cases involved than other studies in China including our previous study (Zhao et al, 2009). In this study risk factors for oral cancer besides tobacco and alcohols were also examined.…”
Section: Discussionmentioning
confidence: 97%
“…[1] Occupational exposure to carcinogens, [2] infections with certain papilloma viruses [3,4] and nutritional status [5] are additional risk factors that have been associated with an increased cancer risk. Poor dental hygiene, accompanied by tooth loss, [6] is another suspected risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HPV had an independent prognostic effect on the overall survival of OSCC after adjusting for other factors, such as histological grade, TNM stage and tobacco use. Another characteristic was the significant correlation with improved survival in OSCC patients (Zhao et al, 2009). In 2001, Schwartz et al also demonstrated that HPV16 presence was independently related to a favorable prognosis in a population of 254 OSCC patients ).…”
Section: Incidence In Oral Tumorsmentioning
confidence: 99%